Competitive strategy to improve the quality of service of a telephone company - Ruiz Paisig, Juana Ximena (2020)
The research had the general objective of proposing a competitive strategy to improve the quality of service of the private company For the practical contribution, Parasuraman's theory is based. The population was made up of all the people who acquire a product or service in the company San José- Movistar Chiclayo. Considering the indicated, the population is infinite, having as sample 196 clients. The research was descriptive proactive; To determine the instrument's reliability coefficient, it was analyzed using the cronbach alpha, resulting in 0.870; For the procedure, the statistical program SPSS 25.0 and EMP were used. Finding the following results: In table 6, with respect to the quality of services, it is 57%, indicating the quality of the services of the Movistar company, they are not effectively in all aspects, so they evaluate it now the lowest in the aspect of quality, as there is also another part of the clients that evaluate the quality of services of the Movistar company high at a high level, which concludes that the majority of the client population are dissatisfied with the quality of services provided by said company.